Factors associated with obstetric fistula repair failure among women admitted at Gynocare Women’s and Fistula Hospital in Kenya, 2012-2016: a case control study - Mwangi, Henry Ruiru; Wang'ombe, Ann; Mabeya, Hillary; Kipruto, Hillary; Wanjala, Anthony (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: Determine factors associated with obstetric fistula repair failure at Gynocare Women’s & Fistula Hospital in Kenya. Methods: This was a case-control study whosestudy population was patients who underwent repair at Gynocare between January, 2012 to December, 2016; 119 cases and 238 controls were selected by simple random sampling out of 357 cases. Results: Study participants were mostly (62.2%) married with low or no formal education (90.1%). Delivery that led to fistula development occurred in the hospital for 85.2% of the study participants and 66.7% resulted into C/S. Only 1/3 (n = 120) had previous repair(s).Patients classified to have VVF IIA were 20.5%, class IIB were 35.0% and class III were 9.2%, the rest (35.3%) were classified as class I. The odds of repair failure were 2.9 times more among those with previous repair attempts compared to those with no previous repair attempts. Women with VVF IIB were 4 times more likely to develop failure. While women who attained at least secondary educations were 77% less likely to have fistula repair failure. Conclusions: After controlling the effects of age, marital status, comorbidities, parity, time to repair, and post-operative complications: having not attained at least secondary education level, having previous repair attempts, and VVF IIB were found to be independent predictors of repair failure.